5(B+3)=4(B-7)+2B

Simple and best practice solution for 5(B+3)=4(B-7)+2B equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(B+3)=4(B-7)+2B equation:


Simplifying
5(B + 3) = 4(B + -7) + 2B

Reorder the terms:
5(3 + B) = 4(B + -7) + 2B
(3 * 5 + B * 5) = 4(B + -7) + 2B
(15 + 5B) = 4(B + -7) + 2B

Reorder the terms:
15 + 5B = 4(-7 + B) + 2B
15 + 5B = (-7 * 4 + B * 4) + 2B
15 + 5B = (-28 + 4B) + 2B

Combine like terms: 4B + 2B = 6B
15 + 5B = -28 + 6B

Solving
15 + 5B = -28 + 6B

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Add '-6B' to each side of the equation.
15 + 5B + -6B = -28 + 6B + -6B

Combine like terms: 5B + -6B = -1B
15 + -1B = -28 + 6B + -6B

Combine like terms: 6B + -6B = 0
15 + -1B = -28 + 0
15 + -1B = -28

Add '-15' to each side of the equation.
15 + -15 + -1B = -28 + -15

Combine like terms: 15 + -15 = 0
0 + -1B = -28 + -15
-1B = -28 + -15

Combine like terms: -28 + -15 = -43
-1B = -43

Divide each side by '-1'.
B = 43

Simplifying
B = 43

See similar equations:

| Z^2+8z-16=0 | | (5t)(5t)5= | | 3x-5-2=2(4x-6)+27 | | x^2+9=6v | | v-e=2 | | 2x^2+59=0 | | -(3y+2)-(-2y-4)=-1 | | 1000x^3-27y^3=0 | | 4s^2+36s+81=0 | | 8(3x-9)=4(6x+3) | | x+36=108 | | 4s^2+362=-81 | | 8+15m-3=6m+29-3m | | X^4-25y^4=0 | | 8x-2-x-4x=-3x+14 | | x^3-3x^2+4x+y^3+6y^2+13y+8=0 | | 6p+18p=192 | | (8+3i)(8-3i)=0 | | 4x^2+20x+551=0 | | 2k-8=5-6k | | Log(x)=10 | | -6(2b+4)+(13b-9)=0 | | C(7)=300+7x | | 35x+2=25x-7+15x-8 | | 3.6q-3.1-4.1q=-1.5-3.8 | | v^2+6=-5v | | z^2-bz-az+ab=0 | | =10-4(4+a) | | 4n=-28n-3 | | 3-q+q=4q+27 | | 8a-5=11 | | 53-2d=2+d |

Equations solver categories